2012
DOI: 10.4028/www.scientific.net/kem.527.217
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Tribological Properties of One-Process and Two-Process Textures after Vapour Blasting and Lapping Using Pin-on-Disc Tests

Abstract: Wear tests were conducted using a pin-on-disc tester. In the experiment, a steel disc of hardness 40 HRC was put in contact with a steel pin of hardness 64 HRC with spherical end. Disc samples were prepared in order to obtain very similar values of the Sq parameter of one-process and two-process isotropic surfaces. Height of one–process disc surfaces, characterized by the Sq parameter was in the range 0.5 – 6 µm, but of two-process textures 1- 4.5 µm. Dry and lubricated tests, using different contact condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 11 publications
8
20
0
Order By: Relevance
“…Therefore, the dependence Ssk-VD seems to be more substantial than Sku-VD. Similar results were obtained in [11] and partially in [22] under dry friction conditions and in [12] under lubricated regime. Figure 11.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the dependence Ssk-VD seems to be more substantial than Sku-VD. Similar results were obtained in [11] and partially in [22] under dry friction conditions and in [12] under lubricated regime. Figure 11.…”
Section: Resultssupporting
confidence: 87%
“…In this case the VD parameter obtained 0.777 mm 3 The wear tracks visible on the cross-sectional areas of the discs Figure 5c, d don't have spherical shapes. This may indicate that during the co-acting of the elements, the initial non-conformal contact changed into a conformal [22]. The wear volume of discs was proportional to the volumetric wear of balls; the linear coefficient of correlation was between 0.69 and 0.94.…”
Section: Resultsmentioning
confidence: 99%
“…One can obtain information about wear amount only after measurement of a worn surface. Wear measurement of balls and discs can be typical examples [4]. In the second case surface topography should be measured in the same place before and after friction test.…”
Section: Introductionmentioning
confidence: 99%
“…The probability description of a two-process texture can be used to assess progress of low wear or abrasive machining [17]. It was found that in a regime of starved lubrication the coefficient of friction was proportional to the Spq parameter (3D equivalent to the Rpq parameter) of two-process random isotropic surfaces [18,19]. It is believed that contact characteristics of two-process random textures are governed by the Rpq parameter [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Proper separation of this profile portion is functionally important; the plateau surface part decides about either lubrication or contact of two-process textures [6,18,19,21].…”
Section: Introductionmentioning
confidence: 99%